Insights on Alterations to the Rumen Ecosystem by Nitrate and Nitrocompounds - Latham, Elizabeth A.; Anderson, Robin C.; Pinchak, William E.; Nisbet, David J. (Frontiers in Microbiology, 2016)
Nitrate and certain short chain nitrocompounds and nitro-oxy compounds are being investigated as dietary supplements to reduce economic and environmental costs associated with ruminal methane emissions. Thermodynamically, nitrate is a preferred electron acceptor in the rumen that consumes electrons at the expense of methanogenesis during dissimilatory reduction to an intermediate, nitrite, which is primarily reduced to ammonia although small quantities of nitrous oxide may also be produced. Short chain nitrocompounds act as direct inhibitors of methanogenic bacteria although certain of these compounds may also consume electrons at the expense of methanogenesis and are effective inhibitors of important foodborne pathogens. Microbial and nutritional consequences of incorporating nitrate into ruminant diets typically results in increased acetate production. Unlike most other methane-inhibiting supplements, nitrate decreases or has no effect on propionate production. The type of nitrate salt added influences rates of nitrate reduction, rates of nitrite accumulation and efficacy of methane reduction, with sodium and potassium salts being more potent than calcium nitrate salts. Digestive consequences of adding nitrocompounds to ruminant diets are more variable and may in some cases increase propionate production. Concerns about the toxicity of nitrate’s intermediate product, nitrite, to ruminants necessitate management, as animal poisoning may occur via methemoglobinemia. Certain of the naturally occurring nitrocompounds, such as 3-nitro-1-propionate or 3-nitro-1-propanol also cause poisoning but via inhibition of succinate dehydrogenase. Typical risk management procedures to avoid nitrite toxicity involve gradually adapting the animals to higher concentrations of nitrate and nitrite, which could possibly be used with the nitrocompounds as well. A number of organisms responsible for nitrate metabolism in the rumen have been characterized. To date a single rumen bacterium is identified as contributing appreciably to nitrocompound metabolism. Appropriate doses of the nitrocompounds and nitrate, singly or in combination with probiotic bacteria selected for nitrite and nitrocompound detoxification activity promise to alleviate risks of toxicity. Further studies are needed to more clearly define benefits and risk of these technologies to make them saleable for livestock producers.